2021
DOI: 10.5223/pghn.2021.24.3.316
|View full text |Cite
|
Sign up to set email alerts
|

Growth Patterns of Indonesian Infants with Cow's Milk Allergy and Fed with Soy-Based Infant Formula

Abstract: Purpose The use of soy-based infant formula has increased widely in infants with cow's milk allergy (CMA). This study aimed to provide evidence on the growth pattern of CMA infants fed with soy-based infant formula in an Indonesian setting. Methods A multi-site, intervention study was conducted among full-term and normal birth weight CMA infants. Within six months, the subjects were provided with a soy-based infant formula. Weight, height, and head circumference were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In our study, infants with regular SF intake had significantly heavier body weight at 6 months of age than those without regular SF intake. This is similar to previous findings that SF does not detrimentally affect growth patterns in infants 22,24 . Among the 210 participants who ingested SF in this study, 20 experienced transient gastrointestinal symptoms and one had an FPIES‐type reaction.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, infants with regular SF intake had significantly heavier body weight at 6 months of age than those without regular SF intake. This is similar to previous findings that SF does not detrimentally affect growth patterns in infants 22,24 . Among the 210 participants who ingested SF in this study, 20 experienced transient gastrointestinal symptoms and one had an FPIES‐type reaction.…”
Section: Discussionsupporting
confidence: 91%
“…In a review of 40 studies, Katz et al 21 reported the incidence of soy sensitization from SF to be 8.7%–8.8%. In contrast, a recent Indonesian study showed that SF did not induce allergic reactions to soy 22 . Similarly, an Israeli study demonstrated that the use of SF in the early neonatal period did not increase the prevalence of soy allergy in infants 23 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…12,13 This is due to its allergenicity, being poorly tolerated by 8% to 10% of infants with CMPA. 49,50 Second, low formula costs deflate the total costs associated with SF, masking the increase in healthcare resource consumption due to increased symptoms in children. The current study carries limitations that should be discussed.…”
Section: Discussionmentioning
confidence: 99%